Temporal Augmentation: A Systematic Review - Othman, Sammy; Cohn, Jason E.; Burdett, Jacob; Daggumati, Srihari; Bloom, Jason D. (Facial Plastic Surgery, 2020)
Clinicians employ various modalities in order to achieve temporal augmentation; however, no literature comprehensively describes these methods or provides perspective on available options. Understanding the available methodologies for cosmetic temporal augmentation allows for improved patient satisfaction with limited risk of complications. To synthesize the available literature on cosmetic temporal augmentation, including all available methodologies, patient satisfaction data, and complication rates, as well as to identify gaps in the available literature to encourage further research. A literature search was performed using the databases PubMed, Ovid Medline, Cochrane Library, and Web of Science. Using the key terms “temporal” or “temple” and “augmentation” or “rejuvenation,” all article formats presenting primary literature data involving cosmetic temporal augmentation were included. Articles not presenting patient data or not discussing cosmetic indications were eliminated. A total of 12 articles were deemed appropriate for analysis. Of the 12 articles included, 6 (50%) evaluated filler techniques, 3 discussed fat grafting (25%), and 3 reviewed solid implant (25%) techniques. Eight (67%) of these were retrospective reviews, with the remaining being prospective trials (33%). All studies found high patient satisfaction rates and a small number of complications with their respective methodology. Several methods are employed for cosmetic temporal augmentation, including various types of injectable fillers, solid implants, and fat grafting, with all reporting successful satisfaction and complication outcomes. Further research is necessary to properly compare these modalities. Clinician discretion should guide procedural choice until future well-controlled studies are able to provide standardized outcomes.
Keywords: temporal augmentation; temporal rejuvenation; temporal hollowing; plastic surgery; facial plastic surgery